2008
DOI: 10.3758/cabn.8.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anxiety on task switching: Evidence from the mixed antisaccade task

Abstract: There is behavioral evidence to show that anxiety is associated with an attentional bias for threat-related material (see Bar-Haim, Lamy, Pergamin, BakermansKranenburg, & van IJzendoorn, 2007, for a review). Recent neuroimaging work has also shown that anxiety selectively facilitates early processing of threat and enhances distractibility to task-irrelevant stimuli. According to Bishop (2007; see also Bishop, Duncan, Brett, & Lawrence, 2004), anxiety is associated with enhanced amygdala activation and reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
119
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 43 publications
18
119
5
Order By: Relevance
“…There is much previous empirical support for the predicted adverse effects of anxiety on negative attentional control (see ). However, with the exception of Ansari et al (2008), no published studies have considered the predicted effects of anxiety on positive attentional control. Using There was an interaction between cuing and state anxiety [F(1,45) There was a three-way interaction of complexity, task type, and state anxiety [F(1,45) 4.11, p .04].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is much previous empirical support for the predicted adverse effects of anxiety on negative attentional control (see ). However, with the exception of Ansari et al (2008), no published studies have considered the predicted effects of anxiety on positive attentional control. Using There was an interaction between cuing and state anxiety [F(1,45) There was a three-way interaction of complexity, task type, and state anxiety [F(1,45) 4.11, p .04].…”
Section: Discussionmentioning
confidence: 99%
“…There is hardly any published research on the effects of anxiety on the shifting function. However, Ansari, Derakshan, and Richards (2008), using a mixed antisaccade task, found that highanxious individuals did not show the commonly found switch benefit that results from alternating between antiand prosaccade trials, suggesting that anxiety impaired the shifting function.…”
Section: Apparatus and Designmentioning
confidence: 99%
“…Eysenck et al (2007) argue that the time to respond is an important measure for this efficiency: the more time spent to achieve similar levels of performance accuracy, the less efficient the goal-driven system is. It has been reported for a variety of cognitive tasks that in high-pressure situations performance accuracy can be maintained, but with increased response times relative to low-pressure situations (e.g., Eysenck et al, 2007;Ansari, Derakshan, & Richards, 2008;Derakshan & Eysenck, 2009), although the converse sometimes also occurs: response times are maintained, but accuracy decreases (e.g., Beilock, Kulp, Holt, & Carr, 2004). For motor tasks, high-pressure leads the goal-driven system to invoke a step-by-step control mode, making performance not only significantly slower as in cognitive tasks, but also more prone to error (e.g., Beilock, Bertenthal, McCoy, & Carr, 2004;Masters & Maxwell, 2008).…”
mentioning
confidence: 99%
“…This process results in reduced attentional control and impairment of the inhibition and shifting functions. The inhibition function involves using attentional control in a restraining way to prevent attentional resources being allocated to taskirrelevant stimuli and response (Miyake et al, 2000;Friedman & Miyake, 2004) whereas, the shifting function was described as a positive way to shift the allocation of attention to remain on task-relevant stimuli (Ansari, Derakshan, & Richards, 2008). Eysenck et al (2007) concluded that anxiety may not impair performance effectiveness when it leads to the use of compensatory strategies such as enhanced effort or increased use of processing resources.…”
mentioning
confidence: 99%